Post-Disaster Urban Planning, Cultural Patrimony, and Cusco's Templo de Santiago - Covert, Lisa Pinley (2019)
This article analyzes urban planning and historic preservation following Cusco’s 1950 earthquake through a case study of the Templo de Santiago. Reports and correspondence from various organizations reveals how budgetary decisions and planning goals shaped preservation and development in Cusco. The case of the Templo de Santiago illustrates the challenges faced by neighborhoods affiliated with historic sites that were not priorities for reconstruction or tourism after the earthquake. This case also demonstrates how the language of historic preservation facilitated an economic transformation that went far beyond the scope of post-disaster relief, and that those transformations had long-term implications for cusqueños.